CORRELATION AMONG ZAKAT INFAQ SEDEKAH (ZIS), POVERTY MANAGEMENT FUND (TPF), EDUCATION FUND AND THE NUMBER OF POOR POPULATIONS IN INDONESIA - Nuril Maulydia Aghustin; Eko Fajar Cahyono (Universitas Airlangga, 2020)
The purpose of this study is to know the correlation between ZIS and the number of poor population in Indonesia, the correlation between DPK and the number of poor population in Indonesia, and the correlation between education fund and the number of poor population in Indonesia. The method used is a quantitative method, using a simple correlational approach namely Karl Pearson correlation. The data used is quantitative and includes secondary data taken from the official website of BAZNAS, Ministry of Finance and BPS. This research data includes ZIS in Billion Rupiahs, DPK in Trillion Rupiahs, education fund in Trillion Rupiahs, and poverty rate data in million people. All data is in the period 2002-2019. The results of this study stated that each of the ZIS, DPK, and education fund are closely and significantly related to the negative direction of the number of poor population in Indonesia period time 2002-2019. The results of the correlation coefficient (r) are respectively -0.834, -0.828, and -0.933. The results of the three relationships have a significance probability of 0,000 that is smaller than alpha 0.05. Thus, it can be concluded that the ZIS, DPK, and education fund have an inverse relationship with the number of poor population in Indonesia. In other words, if the ZIS, DPK and education fund increase, the number of poor population in Indonesia will decrease.Keyword: ZIS, Poverty Prevented Fund, Education Fund, and Poverty